Relações lineares entre variáveis meteorológicas e caracteres fenológicos, morfológicos e produtivos em bases genéticas de milho - Loro, Murilo Vieira (2023)
The objective of this work was to verify whether there are linear relationships between meteorological variables and phenological, morphological and productive traits of maize genotypes. Five sowing dates were performed and 71 genotypes were evaluated on September 21, 2021 and 78 genotypes on October 20, 2021, November 20, 2021, December 20, 2021 and January 30, 2022. Each genotype was phenologically characterized at each sowing date. Plant height was obtained from the average of five plants per genotype. Grain yield was evaluated from all plants in the plot, corrected to 13% moisture. With the duration of the phenological stages, the accumulated global solar radiation and the thermal sum in the vegetative and reproductive stages were calculated. Descriptive statistics were calculated. Principal component analysis was applied in order to verify possible formation of groups between sowing dates and genetic bases. Coefficients of linear variation between pairs of variables in each seeding data were calculated. The maize genotypes, sown in September, with shorter duration of the vegetative and reproductive stages, accumulate less global solar radiation and thermal sum and present greater height and grain yield. The maize genotypes, sown in October, November and December, which present in the vegetative stage, shorter duration and lower accumulation of global solar radiation and thermal sum, and in the reproductive stage, greater duration and greater accumulation of global solar radiation and thermal sum, are the most productive. For sowings in January, there are no linear associations between meteorological variables and phenological, morphological and productive traits of maize genotypes. Single, triple, and double hybrids and maize varieties show similar responses to the effects of meteorological variables.